Estrutura trófica e processamento foliar em riachos sob influência do uso do solo. - Cionek, Vivian de Mello (2016)
Headwater streams contributes greatly to the conservation of ecological balance in drainage networks through water recharge and nutrients inputs. The maintenance of ecological balance in these systems is intimately related to forest preservation in their watershed. Despite the benefits and importance of streams, its conservation has been historically neglected. Land use changes such as pasture farming, sugar cane cultivation and urbanization are amongst the main impacts to which streams are subjected. We conducted the present research in order to contribute with the comprehension of the effects and magnitude of land use impacts over integrated ecosystem level responses in streams. We investigated the trophic structure of the aquatic systems. Trophic structure varied accordingly to local influences, rather than land use influences, with the potential contribution of basal resources derived from groundwater. We evaluated if ecosystem functioning was altered due to land use change, through leaf litter breakdown rates. Land use type affected leaf litter breakdown through negative effects over Stenochironomus sp., which represents the main actor in the ecosystem process. The results obtained through both approaches evidenced the effects and magnitude of anthropic impacts acting over streams, integrating biological and environmental responses and contributing with further understanding of stream functioning.